Oocyte Maturation and Fertilization - A Long History for a Short Event - Tosti, Elisabetta (Bentham Science Publishers, 2011)
Events of reproduction occurring from meiotic resumption of the immature oocyte up to its exit from the second meiotic block following activation will be revealed. Morphological modifications of the oocyte during maturation will be related to signal transduction mechanisms involving primary or secondary messengers. A detailed view will be addressed to genetic and epigenetic control of oocyte maturation. At fertilization, reciprocal gamete activation and novel knowledge related to sperm factor and cascade mechanisms occurring in the oocyte will be focused. A detailed description of ion currents occurring during fertilization will depict another point of view of oocyte activation mechanisms, further supporting for their complexity.